Targeted therapies for the treatment of non-small-cell lung cancer: Monoclonal antibodies and biological inhibitors - Silva, Ana P. S.; Coelho, Priscila V.; Anazetti, Maristella; Simioni, Patricia U. [UNESP] (Taylor & Francis, 2017)
The usual treatments for patients with non-small-cell lung cancer (NSCLC), such as advanced lung adenocarcinoma, are unspecific and aggressive, and include lung resection, radiotherapy and chemotherapy. Recently, treatment with monoclonal antibodies and biological inhibitors has emerged as an effective alternative, generating effective results with few side effects. In recent years, several clinical trials using monoclonal antibodies presented potential benefits to NSCLC, and 4 of them are already approved for the treatment of NSCLC, such as cetuximab, bevacizumab, nivolumab and pembrolizumab. Also, biological inhibitors are attractive tolls for biological applications. Among the approved inhibitors are crizotinib, erlotinib, afatinib and gefitinib, and side effects are usually mild to intense. Nevertheless, biological molecule treatments are under development, and several new monoclonal antibodies and biological inhibitors are in trial to treat NSCLC. Also under trial study are as follows: anti-epidermal growth factor receptor (EGFR) antibodies (nimotuzumab and ficlatuzumab), anti-IGF 1 receptor (IGF-1R) monoclonal antibody (figitumumab), anti-NR-LU-10 monoclonal antibody (nofetumomab) as well as antibodies directly affecting the cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) molecule (ipilimumab and tremelimumab), to receptor activator of nuclear factor-kappa B ligand (RANKL) (denosumab) or to polymerase enzyme (veliparib and olaparib). Among new inhibitors under investigation are poly-ADP ribose polymerase (PARP) inhibitors (veliparib and olaparib) and phosphatidylinositol 3-kinase (PI3K) inhibitor (buparlisib). However, the success of immunotherapies still requires extensive research and additional controlled trials to evaluate the long-term benefits and side effects.
Keywords: biological inhibitor; biological therapy; carcinogenesis; lung cancer; monoclonal antibody; non- small- cell lung cancer